In search of appropriate environment for the retirees in Malaysia - Abdul Majid, Noor Hanita; Hamidi, Mohd Hazwan; Denan, Zuraini (2010)
The increasing number of elderly in our country indicates the demand of care facilities to support the lifestyle and well being of the elderly. Today, the young working generations is more career minded and engrossed with their work and life. Unfortunately, the old parents were less attended, visited and some were ignored by their children. Placing their parents at adult-health care facilities, where their parents health and welfare will be prioritized has been assumed as the best choice and place for their aging parents. However, the existing elderly and retirement homes are not suitable for all elderly, particularly the muslim. In Malaysia, the culture and religion are significant criteria to be considered in the formulation of the facilitiesfor the elderly and retirees. Most of retireement home built have not fully focused on the need of religion, especially in catering the Muslim occupants' need. As today's elderly and retirees are more educated and have been professionals during their working age, a new concept and living of retirement home have to be considered. Commonly, the middle ages (age 20's to 50's) malaysian Muslim will be industriously earning money a their develop their families and only when retired will they have more time for themselves and spend more time for religious needs. Hence, once retired, they will change from the busy working life to less or simpler daily activities, running in slow pace and spend more time on religious practices. Therefore, the criteria of new retirement home should been developed from this understanding with underlying islamic principles as guidance. This paper explores ideas on new concepts for retirement centre in Malaysia based on Al-Quran and Al hadith. Responses from questionnaire surveys are analyzed to strengthen the recommended concept and criteria for consideration for the provision of the retirement villages/homes. The findings indicates that a resort like environment, strong spiritual support and close family and community bond and accessibility to medical facilities are among the important criteria of the new retirement home concept.